Understanding participation dilemmas in community mobilisation: can collective action theory help?. Issue 1 (30th October 2018) - Gram, Lu; Daruwalla, Nayreen; Osrin, David
Abstract : Community mobilisation interventions have been used to promote health in many low-income and middle-income settings. They frequently involve collective action to address shared determinants of ill-health, which often requires high levels of participation to be effective. However, the non-excludable nature of benefits produced often generates participation dilemmas: community members have an individual interest in abstaining from collective action and free riding on others' contributions, but no benefit is produced if nobody participates. For example, marches, rallies or other awareness-raising activities to change entrenched social norms affect the social environment shared by community members whether they participate or not. This creates a temptation to let other community members invest time and effort. Collective action theory provides a rich, principled framework for analysing such participation dilemmas. Over the past 50 years, political scientists, economists, sociologists and psychologists have proposed a plethora of incentive mechanisms to solve participation dilemmas: selective incentives, intrinsic benefits, social incentives, outsize stakes, intermediate goals, interdependency and critical mass theory. We discuss how such incentive mechanisms might be used by global health researchers to produce new questions about how community mobilisation works and conclude with theoretical predictions to be explored in future quantitative or qualitative research.